Notes on Syllable Structure in Three Arabic Dialects - Kenstowicz, Michael (Revue québécoise de linguistique, 1986)
AbstractThis paper examines a number of pervasive syllable-based alternations in three modern Arabic dialects: Levantine, Bani-Hassan (Bedouin) and Sudanese. The first part develops a distinction between core (CV, CVV, CVC) and marginal (CVCC, CVVC) syllables. It is argued that core syllables are constructed in the lexical phonology while marginal syllables are built postlexically. The second part of the paper develops an analysis of wasla ("joining"). It is shown how drawing a distinction between the segmental and skeletal tiers helps to explain several properties of this otherwise puzzling phenomenon.